MORFOLOGI SERBUK SARI (POLEN) FAMILI MYRTACEAE: Psidium guajava, Syzygium aqueum, dan Syzygium malaccense - Permatasari, Ira; Rangkuty, Silvia Abni; Fitriani, Devi; Priyanti, RA (Fakultas Biologi Universitas Jenderal Soedirman, 2024)
The Myrtaceae family is one of the families of the Myrtales order. There are two commonly found genera of the Myrtaceae family, namely Syzygium and Psidium. Pollen morphology of 3 species of the Myrtaceae family, namely Psidium guajava, Syzygium aqueum, and Syzygium malaccense were observed using a binocular light microscope. The research conducted aims to see the morphological characteristics of pollen from the three species of the Myrtaceae family. Morphological similarities of pollen from guava (Psidium guajava), water guava (Syzygium aqueum), and bol guava (Syzygium malaccense) are found in the unit, shape, size, polarity, aperture type, and exine ornamentation.